2012
DOI: 10.1016/j.aller.2011.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of angiotensin converting enzyme gene polymorphism and susceptibility to bronchial asthma among Egyptians

Abstract: The results of our study indicate that ACE gene polymorphism is not significantly associated with bronchial asthma or with its severity among Egyptian adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Considering that it has been suggested that the deviation from the expected genotypic frequencies based on the HWE may be a sign of genotyping error [2], I think that during genotyping some kinds of errors occurred. My suggestion might be confirmed by comparison between the studies of Hassanin et al [1] with other reports from Egypt [3][4][5][6][7] on the prevalence of the D allele. It should be noted that the study of Hassanin et al [1] showed a higher prevalence of the D allele (and alternatively a lower prevalence of the I allele) compared with the other studies [3][4][5][6][7].…”
supporting
confidence: 64%
“…Considering that it has been suggested that the deviation from the expected genotypic frequencies based on the HWE may be a sign of genotyping error [2], I think that during genotyping some kinds of errors occurred. My suggestion might be confirmed by comparison between the studies of Hassanin et al [1] with other reports from Egypt [3][4][5][6][7] on the prevalence of the D allele. It should be noted that the study of Hassanin et al [1] showed a higher prevalence of the D allele (and alternatively a lower prevalence of the I allele) compared with the other studies [3][4][5][6][7].…”
supporting
confidence: 64%
“…In the field of asthma, a large number of studies, mainly in Chinese, correlates the D allele with its pathogenesis (37,39,(104)(105)(106)(112)(113)(114), underpinning the fact that individuals carrying the DD genotype are at up to a 60% higher risk of asthma development (37). On the other hand, studies in South Korea, Egypt, Japan and Turkey agree that ACE I/D is not associated with asthma development (107)(108)(109)115), while within the Pakistani population the I allele unexpectedly appears to be a predisposing factor and the D allele a possible protective trait (111).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies on the positive correlation between the ACE I/D variation and asthma pathogenesis come from China, while studies on populations from certain other countries appear to have produced contradicting results. More specifically, case-control studies on population samples from South Korea, Egypt and Japan conclude that this particular ACE polymorphism is not associated with asthma development (107)(108)(109). A relevant study in Turkey, in which researchers also measured enzyme activity in the participating subjects, did not show significant differences in allele distribution between patients and controls, but the ACE activity was significantly increased in patients with asthma (110).…”
Section: Asthma and Ace I/d Polymorphismmentioning
confidence: 99%
“…On the other hand, some studies failed to establish any associations of ACE gene polymorphisms with BA. For instance, ACE gene polymorphism is not significantly associated with BA or with its severity among Egyptian adults [39]. Similarly, the ACE genotype frequencies also do not significantly differ between the patients with BA and healthy controls in study conducted in Turkey [40], Iran [41], and Japan [42].…”
Section: Introductionmentioning
confidence: 84%